IMPLEMENTASI KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMPERKUAT KEDISIPLINAN SISWA MELALUI KEGIATAN SEKOLAH HARIAN DI MAN 1 KAB. SERANG: ABSTRACT, PENDAHULUAN, RUMUSAN MASALAH, TUJUAN PENELITIAN, METODE PENELITIAN, HASIL DAN PEMBAHASAN, KESIMPULAN, DAFTAR PUSTAKA - Chika Syahfitri; Avilianti Pratiwi; Selnistia Hidayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study investigates the implementation of principal leadership in reinforcing student discipline through daily school activities at MAN 1 Serang Regency. The research focuses on leadership strategies, managerial practices, and the principal’s decision-making Processes in cultivating a disciplined school culture. Employing a qualitative descriptive approach, data were gathered through observations, interviews, and documentation. The findings demonstrate that the principal plays a pivotal role in planning, organizing, coordinating, and supervising various daily activities, including morning assemblies, attendance monitoring, habituation programs, and character-building routines. These initiatives significantly contribute to enhancing student punctuality, compliance with school regulations, and overall behavioral discipline. The study concludes that the effective implementation of instructional and transformational leadership is a key determinant in strengthening student discipline and fostering a positive learning environment at MAN 1 Serang Regency.